Differential Thresholds of Proteasome Activation Reveal Two Separable Mechanisms of Sensory Organ Polarization in C. elegans - Kunz, Patricia; Lehmann, Christina; Pohl, Christian (Frontiers in Cell and Developmental Biology, 2021)
Cephalization is a major innovation of animal evolution and implies a synchronization of nervous system, mouth, and foregut polarization to align alimentary tract and sensomotoric system for effective foraging. However, the underlying integration of morphogenetic programs is poorly understood. Here, we show that invagination of neuroectoderm through de novo polarization and apical constriction creates the mouth opening in the Caenorhabditis elegans embryo. Simultaneously, all 18 juxta-oral sensory organ dendritic tips become symmetrically positioned around the mouth: While the two bilaterally symmetric amphid sensilla endings are towed to the mouth opening, labial and cephalic sensilla become positioned independently. Dendrite towing is enabled by the pre-polarized sensory amphid pores intercalating into the leading edge of the anteriorly migrating epidermal sheet, while apical constriction-mediated cell–cell re-arrangements mediate positioning of all other sensory organs. These two processes can be separated by gradual inactivation of the 26S proteasome activator, RPN-6.1. Moreover, RPN-6.1 also shows a dose-dependent requirement for maintenance of coordinated apical polarization of other organs with apical lumen, the pharynx, and the intestine. Thus, our data unveil integration of morphogenetic programs during the coordination of alimentary tract and sensory organ formation and suggest that this process requires tight control of ubiquitin-dependent protein degradation.